(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2021)
The process of coordination and joint cooperation between SAIs and internal auditors in the public sector is considered one of the very important matters in performing efficient audits and are of high quality, especially if this coordination and cooperation is implemented in accordance with international standards, as it leads to avoiding duplication in auditing work. And the distribution of work in a distribution that achieves the objectives of auditing in general and is of general benefit to the economic unit. The research problem lies in the weakness of the relationship between internal auditing and external auditing as a result of not applying INTOSAI Standard (9150) coordination and joint cooperation between SAIs and internal auditors, thus negatively affecting the quality of auditing. In order to address the research problem, the researcher sought to achieve a set of objectives represented in highlighting the importance of coordination and joint cooperation between internal auditing and external auditing, as well as highlighting the effect of coordination and joint cooperation on audit quality. The research reached a number of conclusions, the most important of which is the lack of communication about planning such as joint meetings, as these organizational factors are considered to have a clear impact on the quality of auditing, as well as the absence of joint training programs between SAIs and internal auditors.